Fabrication and evaluation of polylactic acid/ pectin composite scaffold via freeze extraction for tissue engineering - Anwar Hamzah, Mohd Syahir; Abd Razak, Saiful Izwan; Abdul Kadir, Mohammed Rafiq; Mohd Bohari, Siti Pauliena; Mat Nayan, Nadirul Hasraf; Thangaraj Anand, Joseph Sahaya (DE GRUYTER, 2020)
This work reports the fabrication and characterizations of porous scaffold made up of polylactic acid (PLA) with the inclusion of pectin (1, 3, 5, 7, 9, 11wt%) for potential tissue engineering material. The composite scaffold was prepared using a facile method of freeze extraction. Based on the physical evaluations, the scaffold was suggested to be optimumat 5 wt%of pectin loading.Water contact angle of the scaffold was significantly reduced to 46.5o with the inclusion of 5 wt% of pectin. Morphological and topographic of the PLA scaffold revealed that the pectin induced more porous structure and its surface became rougher which was suitable for cell attachment and proliferation. In vitro studies of the PLA/pectin composite scaffold using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromidelt (MTT) assay revealed good biocompatibility whereas Live-Dead kit assay resulted in 91%cell viability after 7 days of incubation.